About the role of typical spacer/crosslinker on the design of efficient magnetic biocatalysts based on nanosized magnetite - Nicolás, Paula; Lassalle, Verónica Leticia; Ferreira, María Luján (Journal of Molecular Catalysis B: Enzymatic)
The immobilization of Candida antarctica lipase B (CALB) was carried out using glutaraldehyde (GLUT) and/or 3-aminopropyl-triethoxisilane (APTS). The aim of this work was to elucidate the role of these crosslinkers/functionalizers on the efficiency of the prepared nanosized catalysts in solvent-free oleic acid esterification.A series of biocatalysts were prepared in presence or absence of GLUT and APTS. The impact of the amount of initial CALB was also explored. An experimental design was utilized to study the variables that maximize biocatalyst activity.A strong dependence of enzymatic activity with the nominal amount of GLUT as well as the final protein/CALB loading was found. Nominal quantity of APTS did not affect catalyst́s activity when used in combination with GLUT. Additional studies demonstrated that stability during storage was mainly dependent on the enzyme loading. The optimum biocatalyst was reused 6 cycles without mass loss. Biocatalyst́s performance decreased with reuse. Mechanisms justifying these results were proposed.The role of GLUT and APTS on stability during storage and on differences between initial enzymatic activity and the performance in the reaction after two months was discussed. The problem of mixed interaction of CALB (covalent bonding plus simple adsorption) was carefully addressed to explain leaching of the lipaseLeaching and stability on storage should be included in the analysis of modifiers impact when support́s modifiers are used. The fresh and stored biocatalyst enzymatic activity has to be addressed looking at the practical aspects of implementation in technological settings. Fil: Nicolás, Paula. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Planta Piloto de Ingeniería Química. Universidad Nacional del Sur. Planta Piloto de Ingeniería Química; Argentina Fil: Lassalle, Verónica Leticia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. ...